Role of oceanic fronts in enhancing phytoplankton biomass in the eastern Arabian Sea during an oligotrophic period. (September 2020) - Kurian, Siby; Chndrasekhararao, A.V.; Vidya, P.J.; Shenoy, Damodar M.; Gauns, Mangesh; Uskaikar, Hema; Aparna, S.G.
Abstract: In the present study, using in-situ and satellite observations, we investigate the influence of physical processes on the enhancement of phytoplankton biomass in the eastern Arabian Sea (EAS). Water column measurements were carried out from 9⁰N to 21⁰N (stations II-2 to II-14) along 68⁰E transect in the EAS during the beginning of fall intermonsoon (FIM) of 2014. Both in-situ and satellite-derived chlorophyll a (Chl a ) showed higher biomass at 15⁰N (station II-8) compared to northern and southern stations. We explored the possible physical processes which can lead to high biological productivity at this station. Our study shows that nearly two times enhancement in Chl a at station II-8 was contributed by an open-ocean front, which occurred two days before the measurement. Based on phytoplankton marker pigments, it was evident that haptophytes were abundant at II-8 with a minor contribution from diatoms and dinoflagellates. This condition also led to a high concentration (4.9 nM) of dimethylsulphide (DMS), an anti-green house gas with a net flux of 3.76 μmol m −2 d −1  at this site. Among the picophytoplankton, Synechococcus were abundant at this station, however Prochlorococcus were absent as confirmed by both marker pigment and flow cytometric counts. The case study presented here demonstrates the dynamic nature of open ocean fronts and their overall contribution to the productivity of the eastern Arabian Sea during the oligotrophic inter-monsoon period. Highlights: Our studies showed that open-ocean fronts can enhance the biological productivity in the EAS even during oligotrophic periods. Abundance of haptophytes at the frontal region might have contributed to high DMS concentration and flux. Among the picophytoplankton,   Synechococcus were abundant at the frontal region, however  Prochlorococcus were absent . A significant increase in TBC supported the dominance of the microbial loop in the region influenced by the frontal system.